Pengaruh Penambahan Serat Ijuk Dan Plasticezer Sebagai Bahan Tambah Terhadap Nilai Karakteristik Beton - Ahmad Ahmad; Jasman Jasman; Hamsyah Hamsyah (Asosiasi Riset Ilmu Teknik Indonesia, 2024)
Concrete is an artificial stone made from a mixture of cement, sand, aggregate and water. For this reason, this construction material is considered very important to continue to be developed. One effort to develop is by improving the weak properties of the concrete itself. From this, researchers will use additional materials such as fiber palm fiber and sika visconcrate in the concrete mixture. Fiber fiber itself has durable properties and does not rot easily in open conditions or embedded in the ground, while sika visconcrate is a chemical that is used as an additive in the mixture to increase the workability, quality and strength of concrete with the desired properties. The method used in this research is quantitative experimentation. The aim of this research is to determine the characteristics of concrete using palm fiber and sika visconcrate with variations of 3%, 5% and 7% from normal concrete. The results of the research show that the average compressive strength of normal concrete is 25,572 MPa, 3% SI+SV variation concrete has an average of 27,365 MPa, 5% SI+SV variation concrete has an average of 26,704 MPa, and 7% SI+ SV variation concrete The average is 26,044 MPa. The split tensile strength test results of normal concrete averaged 6.074 MPa, 3% SI+SV variation concrete averaged 6.444 MPa, 5% SI+SV variation concrete averaged 7.852 MPa, and 7% variation concrete averaged amounting to 8,148 MPa.